1992
DOI: 10.1042/bj2840749
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning of human and rat brain myo-inositol monophosphatase. Expression and characterization of the human recombinant enzyme

Abstract: Inositol monophosphatase (EC 3.1.3.25) is a key enzyme in the phosphoinositide cell-signalling system. Its role is to provide inositol required for the resynthesis of phosphatidylinositol and polyphosphoinositides. It is the probable pharmacological target for lithium action in brain. Using probes derived from the bovine inositol monophosphatase cDNA we have isolated cDNA clones encoding the human and rat brain enzymes. The enzyme is highly conserved in all three species (79% identical). The coding region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 26 publications
7
79
2
Order By: Relevance
“…The K m and V max values for myo-inositol 1-phosphate were calculated as 0.071 Ϯ 0.008 mM and 12.3 Ϯ 0.4 mol/min per mg, respectively. These values are close to the reported kinetic parameters of mammalian inositol monophosphatase, that is, 0.075 Ϯ 0.003 mM (K m ) and 36.8 Ϯ 1 mol/min per mg (V max ) for the recombinant human inositol monophosphatase (22) and 0.16 Ϯ 0.02 mM (K m ) and 13.3 Ϯ 0.9 mol/min per mg (V max ) for bovine brain inositol monophosphatase (7). These data demonstrated that the SuhB protein, in these in vitro experiments, hydrolyzes the ester bond of myo-inositol 1-phosphate as effectively as mammalian enzymes do.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The K m and V max values for myo-inositol 1-phosphate were calculated as 0.071 Ϯ 0.008 mM and 12.3 Ϯ 0.4 mol/min per mg, respectively. These values are close to the reported kinetic parameters of mammalian inositol monophosphatase, that is, 0.075 Ϯ 0.003 mM (K m ) and 36.8 Ϯ 1 mol/min per mg (V max ) for the recombinant human inositol monophosphatase (22) and 0.16 Ϯ 0.02 mM (K m ) and 13.3 Ϯ 0.9 mol/min per mg (V max ) for bovine brain inositol monophosphatase (7). These data demonstrated that the SuhB protein, in these in vitro experiments, hydrolyzes the ester bond of myo-inositol 1-phosphate as effectively as mammalian enzymes do.…”
Section: Resultssupporting
confidence: 64%
“…As is the case for other inositol monophosphatases, this activity was totally dependent on Mg 2ϩ and the optimal concentration of Mg 2ϩ was 10 mM (data not shown). This value is slightly higher than the reported values of 3 mM for the bovine inositol monophosphatase (11) and of 1 mM for the human enzyme (22). At higher concentrations of Mg 2ϩ , this activity was inhibited (data not shown).…”
Section: Resultscontrasting
confidence: 52%
“…Purification of wild-type and mutant InsPase expressed in Escheriuhia coli was carried out as described by McAllister et al (1992). The wild-type and mutant enzymes were purified to homogeneity as judged by SDS/PAGE.…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…The plasmid DNA encoding the mutant Cys218+Ala (C218A) was supplied by P. Greasley and M. Gore (University of Southampton). For the construction of other mutants, oligonucleotide-directed mutagenesis was camed out by the method of Kunkel (1987) using the pRSET vector containing the gene encoding human brain InsPase (McAllister et al, 1992). The following oligonucleotides were synthesized on an Applied Biosystems 380 DNA synthesizer to introduce the corresponding mutation : S'TGGAGAACTTATCAGCATAAC3' CAGATTCATCACCAATGAA3' (E70D), S'ATCAATAGG-GTTAATGATCCA3' (DYON), S'AGTTGTTCCATTAATA-GGGTC3' (D93N), S'AAAGTTAGTTGCTCCATCAAT3' (T95A), S'CAAAGTTAGTTGATCCATCAA3' (T95S) and S'ATCCCAGCACTGAATTCCCAT3' (H217Q).…”
Section: Mutagenesismentioning
confidence: 99%
“…3.5, McAllister et al, 1992;pIC50 3.2, Ohnishi et al, 2007) than IMPase 2 (pIC50 1.8-2.1, Ohnishi et al, 2007). IMPase activity may be inhibited competitively by L690330 (pKi 5.5, McAllister et al, 1992), although the enzyme selectivity is not yet established. Protein serine/threonine kinases (E.C.…”
Section: Anaphylatoxinmentioning
confidence: 99%